Preparasi Dan Karakterisasi Poliuretan Dengan Penambahan Logam Aluminium Sebagai Adsorben Asap Rokok - Yusnidar, Erika; Syahputra, Ricky Andi; Purba, Jamalum; Sutiani, Ani; Pulungan, Ahmad Nasir (Program Studi Pendidikan Kimia, FKIP, Universitas Riau, 2025)
Tobacco smoking is known to have adverse health effects, including an increased risk of cancer , cardiovascular diseases, and respiratory disorders. These health risks are largely attributed to the presence of toxic compounds in tobacco smoke, such as polycyclic aromatic hydrocarbons (PAHs) and cyanide, both of which are carcinogenic. One potential method to mitigate these harmful effects is by using adsorbent materials, such as polyurethane foam, as smoke filters. This study aims to: (1) analyze the characteristics of polyurethane foam modified with aluminum metal, (2) evaluate the adsorption capability of the material against carcinogenic compounds in cigarette smoke using GC-MS analysis, and (3) determine the optimal adsorbent composition for maximum foam performance. Material characterization was conducted using FTIR to identify functional groups, swelling degree tests to assess water absorption capacity, SEM-EDX to examine surface morphology and aluminum distribution, and GC-MS to identify the carcinogenic compounds adsorbed. FTIR analysis revealed the presence of N-H, C-H, C=O, and C-C functional groups in the polyurethane structure. The swelling degree test showed a positive result, indicating good water absorption ability. SEM-EDX analysis demonstrated that aluminum particles were successfully distributed within the foam’s pores, resulting in smaller pore sizes. Furthermore, GC-MS results confirmed the adsorption of several carcinogenic compounds, including pyridine, eugenol, and benzenamine. These findings suggest that aluminum-modified polyurethane foam has the potential to serve as an effective filtering material to reduce exposure to toxic compounds in tobacco smoke.